1982
DOI: 10.1111/j.1365-2044.1982.tb01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Disoprofol and fentanyl for total intravenous anaesthesia

Abstract: Summary Ninety patients undergoing a variety of surgical procedures were anaesthetised with a disoprofol infusion Key wordsAnaesthetics, intravenous; disoprofol. Analgesic, narcotic; fentanyl.Intravenous anaesthesia without inhalational supplements is theoretically attractive particularly at a time when argument continues over the possible harmful effects of waste anaesthetic gases. The fact that intravenous anaesthesia appears to be used by only a few enthusiasts reflects both the difficulty of some technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…There were no significant differences between the four groups in age, weight, sex, ASA physical (14) 82 (15) 70 (15) 66 (12) 82 (12) 62 (11) Group B (n = 86) 91 (13) 78 (13) 69 (11) 66 (10) 84 (13) 68 (11) Group C (« = 71) 95 (10) 81 (14) 71 (10) 64 (11) 80 (16) 65 (12) Group D (n = 76) 91 (15) 80 (11) 68 (9) 67 (8) 85 (11) 63 (10) status, premedication and duration of anaesthesia (table I). Haemodynamic changes were similar in the four groups (table II) and no patient developed cardiac events associated with lignocaine.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There were no significant differences between the four groups in age, weight, sex, ASA physical (14) 82 (15) 70 (15) 66 (12) 82 (12) 62 (11) Group B (n = 86) 91 (13) 78 (13) 69 (11) 66 (10) 84 (13) 68 (11) Group C (« = 71) 95 (10) 81 (14) 71 (10) 64 (11) 80 (16) 65 (12) Group D (n = 76) 91 (15) 80 (11) 68 (9) 67 (8) 85 (11) 63 (10) status, premedication and duration of anaesthesia (table I). Haemodynamic changes were similar in the four groups (table II) and no patient developed cardiac events associated with lignocaine.…”
Section: Resultsmentioning
confidence: 90%
“…Several attempts have been made to reduce the incidence of pain, such as prior administration of opioids [15] or aspirin [16], the use of a largegauge cannula [10], injection into a large vein rather than one on the dorsum of the hand [5], 50% dilution in a glucose solution [14], and the use of EMLA cream applied to the skin 1 h before cannulation [6]. The data from all these studies are difficult to compare because of variation in study design.…”
Section: Discussionmentioning
confidence: 99%
“…In a further study, Major et al . induced and maintained anaesthesia with infusions of propofol in 90 (ASA I or II) healthy patients, who were premedicated with pethidine and promethazine [3]. Patients underwent a variety of surgical procedures (some requiring muscle relaxation), breathed oxygen enriched air and received supplementary boluses of fentanyl.…”
mentioning
confidence: 99%
“…Complications with the solvent Cremophor EL led to the formulation of a soy-bean oil emulsion [2]. Clinical studies with both preparations suggested that propofol should serve as a short acting hypnotic drug, ideally suited for day-case anaesthesia [3,4] or other routine operations [5]. Comparison of the two formulations in the literature suggest that, for induction of anaesthesia, the dose requirement of the emulsion form seemed to be higher than that of the Cremophor EL preparation [6,7].…”
mentioning
confidence: 99%